Environment Impact Assessments in developing economies - Lesirma, Simeon (International Journal of Environmental Sciences, 2016)
Purpose: Environmental Impact Assessment (EIA) is scientific and legal system for identifying and introducing measures to prevent environmental adverse impacts caused by development project. Developing countries have continuously and vigorously pursued economic growth; they have awakened to the fact that there is need for environmental compliance. This is evident in the numerous contemporary debates on various environmental issues and the increased awareness among the citizenry about environmental matters. Conclusions: In Africa, many countries have instituted EIA regulations relatively recently. The adoption of EIAs in Africa is the result of a number of recent initiatives, including the 1995 African Ministerial Conference on Environment that committed African environment ministers to formalize the use of EIAs, an EIA stakeholders meeting in Nairobi in 1998, and the work of the Pan-African Initiative for Capacity Development and Linkages for EIA in Africa (CLEIAA).The Asian countries vary in terms of legislation, ranging from none to very recent and not widely applied legislation to extensive and robust EIA regulation set within a broader planning framework (Japan, Hong Kong, South Korea). Briffett asserts that many EIAs in the poorer Asian countries are of inadequate quality, with poor scoping, poor impact prediction, and limited public participation. This is largely attributed to the fact that most of these countries are preoccupied with economic growth, and EIAs are considered potential brakes on economic growth. Policy Recommendations: This study provides implications for both policy and practice. This study recommends that developing countries should borrow a leaf from developed countries on EIA systems in their quest to attain sustainable development.